2022
DOI: 10.1136/bmj.o2141
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan floods pose serious health challenges

Abstract: With a third of Pakistan inundated by the floods that have affected more than 33 million people, local relief workers and public health experts have said that they are fearing a rise in several waterborne and mosquito-borne diseases and skin infections. 1 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Further health risks include the potentially stunted growth of children resulting from malnutrition and the disruption of a polio vaccine rollout programme. 25 Damages are expected to exceed preliminary estimates of $10 bn. 26 Pakistan contributes less than 1% of global carbon emissions.…”
Section: Extreme Monsoonal Rainfall and Glacialmentioning
confidence: 99%
“…Further health risks include the potentially stunted growth of children resulting from malnutrition and the disruption of a polio vaccine rollout programme. 25 Damages are expected to exceed preliminary estimates of $10 bn. 26 Pakistan contributes less than 1% of global carbon emissions.…”
Section: Extreme Monsoonal Rainfall and Glacialmentioning
confidence: 99%
“…This is caused by a significant temperature rise in the country during the past 6 decades; the average temperature has risen to half a degree Celsius (Chaudhry et al, 2009), triggering several disastrous events, such as floods, droughts, and biological hazards. Series of extreme droughts in the late 1990s to early 2000s (Khan et al, 2020a), four deadly floods between 2010-2014 and disastrous floods of 2022 (Shah et al, 2021;Sarkar, 2022), and a recent climate-led locust outbreak (Khatri, 2019) are a few examples. Such catastrophes are alarming for a developing nation like Pakistan, which mainly relies on agriculture and associated sectors that are highly sensitive to climatic variations.…”
Section: Introductionmentioning
confidence: 99%
“…During the floods of 2010, Pakistan's agriculture sector faced a loss of over one million hectares of unharvested crops and 1.5 million livestock resulting in a loss of over US$10 billion to the poor economy (Shah et al, 2018). The recent flood of 2022 that wreaked havoc in Pakistan, washing out one-third of the country, displacing three million people, and causing unprecedented loss of human lives, crops, and livestock, is believed to be more disastrous than the historic 2010 floods, which is mainly caused by unexpected monsoon rainfall in the country (Sarkar, 2022). Such calamities are significant threats to people's livelihoods as agriculture provides subsistence to the millions of farm households in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Early estimates indicate that five million people, including children, are at a high risk from the outbreak of waterborne and vectorborne diseases. 5 Doctors and relief workers have reported that many people are experiencing emotional trauma because of the flooding, as well as hundreds of cases of diarrhoea, skin infections, and other waterborne diseases among all age groups. Pregnant and lactating women are at particular risk, with more than 70 000 women expected to deliver in September 2022.…”
mentioning
confidence: 99%
“…Pregnant and lactating women are at particular risk, with more than 70 000 women expected to deliver in September 2022 6. Clean drinking water is not available in areas that were ravaged by floods and there is a risk of outbreaks of diarrhoea, cholera, typhoid, gastroenteritis, dengue, and malaria 57. Diseases like malaria, polio, and covid-19 are more likely to flare up, particularly in camps where water and sanitation facilities have been damaged.…”
mentioning
confidence: 99%